Strategi Pemasaran Budidaya Jamur Tiram Putih (Pluoretus Ostreatus) terhadap Petani di Desa Klumpang Kampung - Raissa Amanda Putri; Budi Askhori Sirait; Audy Andini Lubis; Agusni Firi Hasian Dalimunthe; Jihan Fadhilah Taher (MODELING: Jurnal Program Studi PGMI, 2022)
This service in this paper was carried out in Klumpang Kampung Village, namely in Dusun V. This silver expanse district has many flat areas that are used as agricultural land by the local community. Many people here are farmers in an effort to earn an income. The targets for the participants of this service activity are farmer families with the profile: are small farmers, have a farming business on flat dry land, have no other job besides farming, live in the village where the activity is located, have strong motivation and intentions as well as the ability to improve agricultural productivity, and of course willing to be fostered and willing to follow and implement all programs consistently and responsibly. The beginning of the service activity was preceded by students seeing and paying attention to the mushroom cultivation process which the community explained in detail from beginning to end. One example is assisting in the manufacture of organic fertilizers and oyster mushroom cultivation in wood and polybag fermentation systems, as well as marketing management in an effort to assist farmers in developing income-generating profits from farming. The purpose of this community service is to increase family income in mushroom cultivation business by maximizing marketing in the market. The results of this community service show that the marketing statefi carried out can be said to be successful by looking at the results of demand in the market and the amount of income generated. The implementation of the marketing strategy carried out produces 15-20 kg of oyster mushrooms in a day, with an income profit of Â± Rp. 300,000-400,000 per day after implementing the marketing strategy.